ANALYSIS TRANSLATION OF FIGURATIVE LANGUAGE IN THE NOVEL INFERNO BY DAN BROWN - Erfan Pahlefi; Evert Hilman (IKIP Siliwangi, 2023)
This study aimed to find out the translation methods used by translators in translating figurative language in the novel Inferno by Dan Brown, 2013. This research is based on Newmark's theory in the